2004
DOI: 10.1080/00218460490279233
|View full text |Cite
|
Sign up to set email alerts
|

Crack Growth of Structural Adhesive Joints in Humid Environments

Abstract: The adhesive fracture energy, G c , of aluminium-alloy and steel joints, bonded with a rubbertoughened epoxy adhesive, has been measured using monotonically-loaded tests. Such tests have been conducted at different levels of relative humidity and two surface pretreatments have been employed for the substrates prior to bonding: a simple grit-blast and degrease ('GBD') pretreatment or a silane primer ('GBS') pretreatment. When G c was plotted against the crack velocity, three regions of fracture behaviour could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…These values lead to the conclusion that the epoxy/oxide interfaces will indeed be susceptible to attack and degradation upon exposure to water molecules. These ideas have been supported by the use [18] of surface-analytical methods which confirmed that fracture indeed occurred mainly at the interface between the adhesive and the metallic-oxide layer on the substrate. However, it should be borne in mind that the thermodynamic approach describes the behaviour of the joints at equilibrium (i.e.…”
Section: The 'Gbd'-pretreated Jointsmentioning
confidence: 48%
See 3 more Smart Citations
“…These values lead to the conclusion that the epoxy/oxide interfaces will indeed be susceptible to attack and degradation upon exposure to water molecules. These ideas have been supported by the use [18] of surface-analytical methods which confirmed that fracture indeed occurred mainly at the interface between the adhesive and the metallic-oxide layer on the substrate. However, it should be borne in mind that the thermodynamic approach describes the behaviour of the joints at equilibrium (i.e.…”
Section: The 'Gbd'-pretreated Jointsmentioning
confidence: 48%
“…the RH, are critical factors. Finally, it is noteworthy that these observations imply that, in 'Region I', the water molecules reach the vicinity of the crack tip at a sufficiently fast rate to enable the environmental attack mechanism to occur readily, since the G c versus crack velocity dependence is controlled by the viscoelastic nature of the epoxy adhesive, not by the RH employed [18].…”
Section: Results From Crack Propagation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[19,35] Furthermore, water can swell the adhesive inducing the residual stress in the joint. [3] Finite element studies have revealed that the residual stresses due to swelling were sufficient to cause damage of the adhesive at the end of overlap.…”
Section: Introductionmentioning
confidence: 99%